Associations of air pollution with all-cause dementia, Alzheimer’s disease, and vascular dementia: a prospective cohort study based on 437,932 participants from the UK biobank - Yuan, Shiqi; Huang, Xiaxuan; Zhang, Luming; Ling, Yitong; Tan, Shanyuan; Peng, Min; Xu, Anding; Lyu, Jun (Frontiers in Neuroscience, 2023)
Objective To prospectively assess whether air pollution, including PM2.5, PM10, and NOx, is associated with the risk of all-cause dementia, Alzheimer’s disease (AD), and vascular dementia, and to investigate the potential relationship between air pollution and genetic susceptibility in the development of AD. Methods and results Our study included 437,932 participants from the UK Biobank with a median follow-up period of over 10 years. Using a Cox proportional hazards model, we found that participants exposed to PM2.5 levels of ≥10 μg/m3 had a higher risk of developing all-cause dementia (HR = 1.1; 95% CI: 1.05–1.28; p < 0.05) compared to the group exposed to PM2.5 levels of <10 μg/m3. However, there was no significant association between PM10 levels of ≥15 μg/m3 and the risk of all-cause dementia, AD, or vascular dementia when compared to the group exposed to PM10 levels of <15 μg/m3. On the other hand, participants exposed to NOx levels of ≥50 μg/m3 had a significantly higher risk of all-cause dementia (HR = 1.14; 95% CI: 1.02–1.26; p < 0.05) and AD (HR = 1.26; 95% CI: 1.08–1.48; p < 0.05) compared to the group exposed to NOx levels of <50 μg/m3. Furthermore, we examined the combined effect of air pollution (PM2.5, PM10, and NOx) and Alzheimer’s disease genetic risk score (AD-GRS) on the development of AD using a Cox proportional hazards model. Among participants with a high AD-GRS, those exposed to NOx levels of ≥50 μg/m3 had a significantly higher risk of AD compared to those in the group exposed to NOx levels of <50 μg/m3 (HR = 1.36; 95% CI: 1.03–1.18; p < 0.05). Regardless of air pollutant levels (PM2.5, PM10, or NOx), participants with a high AD-GRS had a significantly increased risk of developing AD. Similar results were obtained when assessing multiple variables using inverse probability of treatment weighting (IPTW). Conclusion Our findings indicate that individuals living in areas with PM2.5 levels of ≥10 μg/m3 or NOx levels of ≥50 μg/m3 are at a higher risk of developing all-cause dementia. Moreover, individuals with a high AD-GRS demonstrated an increased risk of developing AD, particularly in the presence of NOx ≥ 50 μg/m3.